Spontaneous recovery in a case of lupus with severe COVID-19 pneumonia; Do we need to reconsider treatment Protocol? - Pradeepta Sekhar Patro; Samir Sahu; Shawaz Iqbal; Ishwar Chandra Behera; Priyanka Samal; Satyasundar Mohapatra (Indian Journal of Rheumatology)
Individuals with inflammatory rheumatic diseases such as lupus are considered at risk for severe COVID-19 infection due to their immunocompromised state and the use of immunosuppressive treatment. Its impact on lupus is yet to be determined. Herein, we report a case of COVID-19 pneumonia in a 40-year-old female with a history of hypothyroidism and mild pulmonary hypertension who presented with a 4-day history of fever and breathlessness. COVID-19 infection was confirmed by real-time polymerase chain reaction (RT-PCR). On examination, she had a malar rash, short hair, and crepitations on the right side infrascapular and infraaxillary areas. Investigations revealed to have anemia, thrombocytopenia, transaminitis, high ferritin, and low fibrinogen, which were suggestive of cytokine release syndrome. Her antinuclear antibody (ANA) by indirect immunofluorescence on Hep-2 cells was 4+ homogeneous in 1:100 titer dilution and extractable nuclear antigen panel showed antibodies positive for histone, nucleosome, Ro, and smith antigens. The patient was diagnosed with systemic lupus erythematosus (SLE) with severe COVID-19 pneumonia with cytokine release syndrome and managed conservatively without specific antivirals or steroids. Her clinical condition and laboratory parameters improved afterward. On the 12th day, her RT-PCR for COVID-19 was negative and the patient was discharged. This would probably a reference case which showed conservative management can be helpful at times where no definite antiviral therapy has been approved with judicious use of immunosuppressants. Close monitoring of clinical conditions and laboratory parameters are recommended for such autoimmune disorders with COVID-19 infection.